2021
DOI: 10.3389/fcell.2020.631491
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Profiles Analysis Identified a Coding-Non-Coding Signature for Predicting Lymph Node Metastasis and Prognosis in Cervical Cancer

Abstract: Accumulating evidence has shown that lymph node metastasis (LNM) is not only an important prognostic factor but also an indicator of the need for postoperative chemoradiotherapy. Therefore, identifying risk factors or molecular markers related to LNM is critical for predicting the prognosis and guiding individualized treatment of patients with cervical cancer. In this study, we used the machine learning-based feature selection approach to identify eight optimal biomarkers from the list of 250 differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Gene expression and clinical data required for this study were obtained from TCGA database. In previous studies ( Shi et al, 2020 ; Zhang et al, 2020 ; Cao et al, 2021 ; Chen et al, 2021 ; Peng et al, 2021 ), many scholars used TGCA gene data to predict the prognosis of patients with cervical cancer. In our study, four DNA damage repair related genes (HAP1, MCM5, RNASEH2A, CETN2) were found to be significantly associated with prognosis and can be incorporated into the nomogram to predict prognosis stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression and clinical data required for this study were obtained from TCGA database. In previous studies ( Shi et al, 2020 ; Zhang et al, 2020 ; Cao et al, 2021 ; Chen et al, 2021 ; Peng et al, 2021 ), many scholars used TGCA gene data to predict the prognosis of patients with cervical cancer. In our study, four DNA damage repair related genes (HAP1, MCM5, RNASEH2A, CETN2) were found to be significantly associated with prognosis and can be incorporated into the nomogram to predict prognosis stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a large number of reports have found that lncRNAs play important biological functions, and lncRNAs have a wide range of tissue expression profiles and strong tissue expression specificity. Multiple studies have found that lncRNAs play key roles in tumorigenesis and development, and several lncRNAs are differentially expressed in cancers, including cervical cancer (5)(6)(7)(8). For example, the lncRNA LINC00673 has a carcinogenic effect in breast cancer (9,10), lung cancer (11,12), and gastric cancer (13) and exerts a tumor suppressive effect in pancreatic cancer (14).…”
Section: Introductionmentioning
confidence: 99%